Oxford Understanding History 1 - Ismat Riaz (Karachi: Oxford University Press., 2024)
Oxford Understanding History 1 introduces students to the study of history by exploring key historical events, figures, and civilizations from ancient to medieval times. The textbook emphasizes the development of critical thinking skills, encouraging students to analyze historical sources, understand cause and effect, and make connections between past and present. Through engaging narratives, maps, timelines, and illustrations, the book helps students build a strong foundation in historical inquiry. Designed to spark curiosity and promote a deeper understanding of global history, it prepares students for more advanced historical studies while fostering an appreciation for the past.